Person between Transpersonality and pathological loneliness - Vitanov, Rumen (Forum Theologicum Sardicense, 2025)
Rumen Vitanov, Person between Transpersonality and Pathological Loneliness. The article explores the concept of the “person” within existential-humanistic psychology and Christian anthropology by examining two opposing psychodynamic states: overcoming egocentrism and pathological introversion. According to existential psychology, pathological introversion manifests as alienation from the biological environment, the shared social world, and one’s own inner self. In Christian anthropology, pathological selfhood results from drifting away from God through a sinful and passionate life-style. In existential-humanistic psychology, transpersonal development is associated with the process of self-actualization and continuous self-transcendence, which involves expanding the scope and depth of personal identity. From the perspective of Christian anthropology, transpersonal development entails overcoming the limitations of the current human state through the restoration of one’s bond with God.